Persepsi Petani Padi terhadap Sustainable Agriculture di Lahan Rawa Kecamatan Tebas Kabupaten Sambas - Arsita, Three; Komariyati Komariyati; Nugraha, Aditya (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
The agricultural sector plays a strategic role in meeting food needs while maintaining environmental sustainability and community welfare. However, conventional farming practices that rely on chemical inputs have caused various problems, such as soil degradation, loss of biodiversity, and environmental pollution. This condition has encouraged the adoption of the Sustainable Agriculture concept, which emphasizes a balance between ecological, economic, and social aspects. Its successful implementation is strongly influenced by farmers’ perceptions as the main actors. This study aims to analyze rice farmers’ perceptions of the implementation of Sustainable Agriculture in swampy areas of Tebas District, Sambas Regency. The research was conducted from October to November 2025 using a survey method involving 95 farmers selected through the Slovin formula and proportional random sampling technique. Data were collected through observation, interviews, and Likert-scale questionnaires, and analyzed using descriptive analysis and binary logistic regression. The results show that farmers’ perceptions are generally positive, particularly regarding water management, variety selection, and cropping patterns. However, the use of organic fertilizers, environmentally friendly pest control, and post-harvest management are still considered difficult. Education level and non-farming occupations significantly influence farmers’ perceptions. Therefore, enhancing extension services, training, and support for business diversification is necessary to promote the adoption of Sustainable Agriculture.